Learning and teaching in school science : practical alternatives - Watts, Mike. (Milton Keynes : Open University Press, 1989)
This work provides a practical guide to a variety of strategies and classroom activities: a collection of experience and ideas about different teaching methods which should benefit both trainee and practising teachers.
Includes bibliographical references and index.
Keywords: Science -- Study and teaching